Examining Science Teachers’ Decisions about Nuclear Power Plants from the Perspective of Normative Decision Theory - Nurhan Ozturk; Esra Bozkurt-Altan (Journal of Education in Science, Environment and Health)
This study aimed to determine science teachers’ decisions about the socio-scientific issue of nuclear-power plant and how these decisions are given within the framework of the decision making process. The design of this research is based on a case study. 22 teachers who worked in the middle schools in the city center of the province of Sinop were recruited for the study. The data were collected through the semi-structured interviews. The data obtained through these interviews were analyzed qualitatively. For the analysis of the data the opinions of the teachers were discussed according to the steps of the decision-making process based on normative decision theory. The knowledge levels of science teachers about nuclear power plants were mostly found to be partially sufficient. It has been determined that science teachers evaluate the socio-scientific issues of nuclear power plants mostly with the dimensions of economy and environment.